Creating Relegios Character and disipline Through ctivites of Tahfidz Qur"an Kindergarten - Rizka Amalia (JURNAL SOCIUS, 2022)
This study aims to explore the effectiveness of cultivating religious character and discipline through Al-Qur'an tahfidz activities in Al Hamid Kindergarten and Blossom Kindergarten Banjarmasin. The research method used is a multi-site study involving two kindergartens as research locations. Data collection was carried out through observation, interviews, and questionnaires to teachers, parents, and children involved in Al-Qur'an tahfidz activities. The collected data were analyzed descriptively to gain a comprehensive understanding of the effects of cultivating religious and disciplinary character through Al-Qur'an tahfidz activities in Kindergarten. The results showed that the activities of tahfidz Al-Qur'an make a positive contribution in instilling religious character and discipline in children in kindergarten. The children showed an increase in understanding religious values, awareness of moral behavior, and discipline in carrying out daily activities. In addition, through Al-Qur'an tahfidz activities, children also develop a deeper love and interest in the Al-Qur'an as a source of religious teachings. However, there are several challenges faced in implementing Al-Qur'an recitation activities in kindergarten, such as a lack of resources and support from the surrounding environment. Therefore, this study also recommends several strategic steps to increase the effectiveness of the Al-Qur'an tahfidz program in kindergarten, including the active participation of parents in supporting and involving themselves in children's religious activities outside of school. In conclusion, tahfidz Al-Qur'an activities have great potential in cultivating religious character and discipline in kindergarten. Good implementation, parental support, and support from the surrounding environment can increase the benefits of this program. This research is expected to contribute to the development of religious and disciplinary character education at the kindergarten level.